New Straits Times, 26 April 2007 (The New Straits Times Press (M) Bhd, 2007)
Tuanku Mizan Zainal Abidin, the Sultan of Terengganu, will officially ascend the throne as the 13th Yang di-Pertuan Agong today in an installation ceremonu steeped in traditional.